The Role of Social Media in Shaping Adolescents Self-Esteem and Body Image in Urban Pakistan - Arfa Akram ,; Rabail Bashir,; Adeeba Inam,; Junaid Hassan Ayaz,; Anum Fatima Rajwani,; Meer Arsalan khan, (Dialogue Social Science Review (DSSR), 2025)
The research evaluated how social media affects adolescent self-esteem and body image perception among 200 participants throughout urban Pakistan by using a mixed-methods investigation. Sixty-two percent of participants showed declining self-esteem levels because of their habit of using social media frequently. The presence of idealized social media content affected 58% of adolescents because they developed negative perceptions about their body images. Social comparison emerged as a vital element in interview-based qualitative research which also demonstrated the relation between comment and like validation. Results from regression analysis demonstrated that higher social media contact leads to a 35% worsening of body image dissatisfaction in users. This data showed that 65% of adolescents who took part in posting selfies for self-objectification exhibited elevated body surveillance behaviors. The research proves that people need intentional programs about media literacy and self-image health to protect users from social media psychological harm.